2022
DOI: 10.3233/jhd-229006
|View full text |Cite
|
Sign up to set email alerts
|

Huntington’s Disease Clinical Trials Corner: November 2022

Abstract: In this edition of the Huntington’s Disease Clinical Trials Corner, we expand on the PIVOT HD (PTC518), and SIGNAL (pepinemab) trials, and list all currently registered and ongoing clinical trials in Huntington’s disease. We also introduce a ‘breaking news’ section highlighting recent updates about the SELECT HD, uniQure AMT-130, and VIBRANT HD clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 13 publications
0
11
0
2
Order By: Relevance
“…For example, mutant huntingtin protein (mHTT) possibly plays a central and critical role in pathogenic processes of HD and the current exploration of HD therapeutics has shifted towards targeting the pathogenic mutation and aimed to intervene at the RNA and DNA levels to lower huntingtin allele [ 7 , 10 ]. Clinical trials of RNA-targeting approaches including anti-sense oligonucleotide (ASO) [ 24 ], RNA interference (RNAi) [ 25 ] and adeno-associated virus (AAV)-mediated gene therapies [ 26 , 27 ] or preclinical DNA-targeting investigations including zinc-finger nucleases (ZFNs) [ 28 ], CRISPR/Cas9 [ 29 ] and transcription activator-like effector nucleases (TALENs) [ 30 ] all provided new hope for the development of effective treatment for HD. In the meanwhile, this emphasized the potential significance of biofluid biomarkers, especially referring to mHTT, to reflect responses to HTT-lowering treatments and act as a surrogate endpoint in clinical trials of HD now and in the future.…”
Section: Introductionmentioning
confidence: 99%
“…For example, mutant huntingtin protein (mHTT) possibly plays a central and critical role in pathogenic processes of HD and the current exploration of HD therapeutics has shifted towards targeting the pathogenic mutation and aimed to intervene at the RNA and DNA levels to lower huntingtin allele [ 7 , 10 ]. Clinical trials of RNA-targeting approaches including anti-sense oligonucleotide (ASO) [ 24 ], RNA interference (RNAi) [ 25 ] and adeno-associated virus (AAV)-mediated gene therapies [ 26 , 27 ] or preclinical DNA-targeting investigations including zinc-finger nucleases (ZFNs) [ 28 ], CRISPR/Cas9 [ 29 ] and transcription activator-like effector nucleases (TALENs) [ 30 ] all provided new hope for the development of effective treatment for HD. In the meanwhile, this emphasized the potential significance of biofluid biomarkers, especially referring to mHTT, to reflect responses to HTT-lowering treatments and act as a surrogate endpoint in clinical trials of HD now and in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Intracranial administration of AMT130 at two different doses is being tested in two clinical trials including early HD participants (NCT04120493 [ 3 ] and NCT05243017 [ 4 ]). Following a pause in recruitment [ 14 ] the trial was restarted in 2023. Two updates from the sponsor in 2023 showed that following an expected initial increase in CSF NfL shortly after the surgical procedure, the concentrations of the biofluid biomarker returned to baseline concentrations.…”
Section: Breaking Newsmentioning
confidence: 99%
“…A number of low-molecular-weight compounds that bind to splicing factors are currently known; however, they simultaneously modulate splicing of many genes [ 119 ]. Several small molecules have been found that specifically bind to target RNAs [ 98 , 119 , 120 , 121 , 122 ]. The best studied of these, risdiplam, modulates splicing of the SMN2 gene and can be used to treat spinal muscular atrophy [ 121 ].…”
Section: Modulation Of Unproductive Splicingmentioning
confidence: 99%
“…Branaplam, similar in structure and mechanism of action to risdiplam, promotes the inclusion of the cryptic poison exon in the HTT gene, which reduces its expression and slows down the progression of Huntington’s disease [ 122 ]. The small molecule PTC518, which is currently in phase 2 clinical trials, has a similar effect [ 120 ].…”
Section: Modulation Of Unproductive Splicingmentioning
confidence: 99%
See 1 more Smart Citation